Digital Transformation of Women Entrepreneurs in Makassar City: Analysis of Opportunities and Challenges from a Gender Perspective - Yahya, Nurul Fajriah; Tawe, Amiruddin; Rakib, Muhammad; Sulolipu, Andi Annisa (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the digital transformation of women entrepreneurs in Makassar City with a focus on analyzing opportunities and challenges from a gender perspective. Using a qualitative method with a literature study approach, this study analyzed data from various primary and secondary sources for the period 2019-2024. The results showed a significant increase in the adoption of digital technology among women entrepreneurs from 15% to 52%. The main challenges identified include limited access to capital, digital literacy gaps, and socio-cultural factors. The fashion and craft sectors dominate the digital women entrepreneur landscape (35%), followed by culinary (30%). This study identified four key factors for the success of digital transformation: digital skills, business networks, product innovation, and market access. Women entrepreneurs who successfully adopted digital technology recorded an average increase in income of 35%. This study provides strategic recommendations for the development of gender-responsive policies and empowerment programs to support the digital transformation of women entrepreneurs in Makassar.